Continuous glucose monitoring: a review of the evidence, opportunities for future use and ongoing challenges. Issue 5 (2nd May 2018) - Wood, Anna; O'Neal, David; Furler, John; Ekinci, Elif I.
Abstract: The advent of devices that can track interstitial glucose levels, which are closely related to blood glucose levels, on a near continuous basis, has facilitated better insights into patterns of glycaemia. Continuous glucose monitoring (CGM) therefore allows for more intensive monitoring of blood glucose levels and potentially improved glycaemic control. In the context of the announcement on 1 April 2017 that the Australian Government will fund CGM monitoring for people with type 1 diabetes under the age of 21 years, this paper provides a review of the evidence for CGM and some of the ongoing challenges. There is evidence that real‐time CGM in type 1 diabetes improves HbA1c and hypoglycaemia, while in type 2 diabetes, the evidence is less robust. Initial barriers to widespread implementation of CGM included issues with accuracy and user friendliness; however, as the technology has evolved, these issues have largely improved. Ongoing barriers include cost, and weaker evidence for their benefit in certain populations such as those with type 2 diabetes and less glycaemic variability. CGM has the potential to reduce healthcare costs, although real‐world studies, including cost‐effectiveness analyses, are needed in this area.